PENGARUH PIJAT BAYI SEBAGAI TERAPI KOMPLEMENTER TERHADAP DERAJAT DEHIDRASI PADA BAYI DENGAN DIARE AKUT USIA 6 – 24 BULAN - Isuari, Yuktika Nugraha (Coping: Community of Publishing in Nursing; Vol 2 No 2 (2014): JURNAL EDISI MEI-AGUSTUS 2014, 2014)
Baby massage is one of complementary therapy that can increase vagal tone which will cause increased absorption of nutrients and fluid therapy so it helps in reducing and or preventing the occurrence of dehydration. The objective of this research is to discover the effect of baby massage as complementary therapy to dehydration level on baby 6 – 24 months with acute diarrhea. This research used quasi experimental design with pre-test and post-test with control group design. The samples consist of 30 selected babies with purposive sampling technique, which were divided into two groups, namely the control group and the treatment group with 15 samples in each groups. Both of groups was measured by using an observation sheets in accordance to the determination of dehydration level according to WHO (2005) for examine pre-test and post-test dehydration level. Post-test was performed once on the third day counted from the first day of diarrhea and given intervention. Research results using Man Whitney U-Test, found a statistically significant difference, with Z value of -2.408 and p = 0.016 (p value ?0,05) which means that there are any effects of baby massage as a complementary therapy for dehydration level on baby 6 – 24 months with acute diarrhea. Based on the research results, it is advisable to health workers, especially nurses to promote baby massage as a complementary therapy in treating babies with acute diarrhea by optimizing the role of parents.
Keywords: Baby Massage; Acute Diarrhea; Level of Dehydration